Pengaruh Motivasi Belajar Terhadap Hasil Belajar Matematika Siswa Siswa Kelas IV SDN 6 Masbagik Utara Tahun Pelajaran 2022/2023 - Arini Maoza Vidianti; Muhammad Husni; Husnul Mukti; Doni Septu Marsa Ibrahim (LAMBDA : Jurnal Ilmiah Pendidikan MIPA dan Aplikasinya, 2022)
This study aims to determine the effect of learning motivation on mathematics learning outcomes of fourth grade students at SDN 6 Masbagik Utara. The type of research used is descriptive quantitative research with the research design used is correlation. The population in this study used one class with a sample of 20 elementary school students. Data collection techniques using questionnaires, observations, and interviews. The data analysis technique used in this study is the analysis prerequisite test using the normality test, linearity test and hypothesis testing. Normality test using Kolmogorov Smirnov, linear test using simple linear regression analysis, and hypothesis testing using t test with a significance level of 0.05. The results of this study are to test the hypothesis, the effect of learning motivation on student learning outcomes contributes 60.5% and a significant value of 0.000. While the contribution of 10.5% is influenced by other factors outside of this study. So it can be concluded that there is an effect of student learning motivation on student learning outcomes.